Characteristics of self-identified sexual addicts in a behavioral addiction outpatient clinic - Wéry, Aline (J Behav Addict, 2016)
BACKGROUND AND AIMS: Research on sexual addiction flourished during the last decade, promoted by the development of an increased number of online sexual activities. Despite the accumulation of studies, however, evidence collected in clinical samples of treatment-seeking people remains scarce. The aim of this study was to describe the characteristics (socio-demographics, sexual habits, and comorbidities) of self-identified “sexual addicts.” METHODS: The sample was composed of 72 patients who consulted an outpatient treatment center regarding their sexual behaviors. Data were collected through a combination of structured interviewing and self-report measures. RESULTS: Most patients were males (94.4%) aged 20–76 years (mean 40.3 ± 10.9). Endorsement of sexual addiction diagnosis varied from 56.9% to 95.8% depending on the criteria used. The sexual behaviors reported to have the highest degree of functional impairment were having multiple sexual partners (56%), having unprotected sexual intercourse (51.9%), and using cybersex (43.6%). Ninety percent of patients endorsed a comorbid psychiatric diagnosis, and 60.6% presented at least one paraphilia. CONCLUSIONS: Results showed highly different profiles in terms of sexual preferences and behaviors, as well as comorbidities involved. These findings highlight the need to develop tailored psychotherapeutic interventions by taking into account the complexity and heterogeneity of the disorder.